2008
DOI: 10.1111/j.1468-2494.2007.00405_1.x
|View full text |Cite
|
Sign up to set email alerts
|

An animal model assessment of common dye–induced allergic contact dermatitis

Abstract: Dyes are a category of substances capable of inducing allergic contact dermatitis found in a variety of foods, drugs, textiles, cosmetics, and hair dyes. This study tested 33 dyes in guinea pigs using a modified Buehler and Klecak method for open epicutaneous testing. The dyes were tested at an induction concentration of 10% and challenge concentrations of 10.0%, 5.0%, and 2.5%. Nine of the 33 dyes tested produced positive allergic reactions in the guinea pig model (2‐amino‐4‐nitrophenol, 2‐amino‐5‐nitrophenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…1 The Expert Panel reviewed newly available studies since that assessment along with updated information regarding types and concentrations of use. 2 –6 The Expert Panel determined to not reopen this safety assessment. Therefore, the Expert Panel confirmed the original conclusion that HC Yellow No.…”
Section: Resultsmentioning
confidence: 99%
“…1 The Expert Panel reviewed newly available studies since that assessment along with updated information regarding types and concentrations of use. 2 –6 The Expert Panel determined to not reopen this safety assessment. Therefore, the Expert Panel confirmed the original conclusion that HC Yellow No.…”
Section: Resultsmentioning
confidence: 99%
“…The most investigated disperse dyes regarding their sensitizing capacity are Disperse Blue 124 and 106, Disperse Orange 3, and Disperse Yellow 3 . When discussing sensitizing capacity, it is important to know that the investigated substances do not contain other substances, but, in these aforementioned studies, the purity of the tested dyes was not reported.…”
Section: Discussionmentioning
confidence: 99%
“…An extensive search of the world’s literature was performed for studies dated 1997 forward, and new data were found. 4-7 The Expert Panel agreed that an updated search of the published literature did not reveal toxicity data that warrant re-evaluation of the safety of this ingredient in cosmetic products. The Expert Panel did note that the European Union has banned Acid Orange 3 for use in cosmetic products; however, this ban is due to a lack of safety test data and not because of any toxicological findings.…”
mentioning
confidence: 99%
“…An extensive search of the world's literature was performed for studies dated 1997 forward, and new data were found. [4][5][6][7] The Expert Panel agreed that an updated search of the published literature did not reveal toxicity data that warrant reevaluation of the safety of this ingredient in cosmetic products.…”
mentioning
confidence: 99%